Rates of motorcycle helmet use and reasons for non-use among adults and children in Luang Prabang, Lao People's Democratic Republic. (December 2015) - Fong, Michelle; Measelle, Jeffrey; Dwyer, Jessica; Taylor, Yvonne; Mobasser, Arian; Strong, Theresa; Werner, Susanne; Ouansavanh, Siamphone; Mounmingkham, Amphone; Kasuavang, Mai; Sittiphone, Dalika; Phoumesy, Khamhak; et al.
Abstract Background Motorcycles make up 81 % of the total vehicle population and 74 % of road traffic deaths in Lao PDR. Helmets reduce the risk and severity of injuries resulting from motorcycle accidents by 72 %. Although Lao law mandates motorcycle helmet use among drivers and passengers, the prevalence of helmet use in Luang Prabang, Lao PDR is unknown. This project aimed to measure the prevalence of motorcycle helmet use among riders (i.e., drivers and passengers) in Luang Prabang. Methods An observational survey in Luang Prabang was conducted in February 2015 to measure the prevalence of motorcycle helmet use among drivers and passengers. Additionally, non-helmet wearing riders were surveyed to identify the reasons for helmet non-use. Results Of 1632 motorcycle riders observed, only 16.2 % wore helmets. Approximately 29 % of adults wore helmets while less than 1 % of all children wore helmets. When surveyed about attitudes towards helmet use, the majority of adult drivers indicated that they did not like how adult helmets feel or made them look. Additionally, almost half of motorcyclists who did not own child helmets reported that their child was too young to wear a helmet. Conclusions Our finding that children wear helmets at significantly lower rates compared to adults is consistent with findings from neighboring countries in Southeast Asia. Results of this study have implications for public health campaigns targeting helmet use, especially among children.